Teologi Corona (Studi Pandangan Mubalig Kota Tanjungpinang Terhadap Covid-19) - Muhammad Alfan Sidik; Nur Ikhlas; Zulfah Zulfah; Romi Aqmal; Andru Lumintang; Ezah Fatmatus Saruroh (Tasamuh: Jurnal Studi Islam, 2023)
This study is about the theological views of mubalig on Covid-19 in the City of Tanjupinang, this research is a field research using theological theory related to the theological schools that developed in Islam, namely Qadariyah, Jabariyah and Ahlussunah and also the theory of the relationship between religion and science from Ian Barbour . This research resulted in the conclusion that: First; The view of the mubalig in responding to the theological views of the community on Covid-19, they have the theological view of Ahlussunah or Asy'ariyah, namely being trusting in Allah but also making efforts in tackling the Covid-19 outbreak by following health protocols. Second; most of their views individually/personally when they see this Covid-19 as a punishment or a trial/test from God, they view more of a trial/test from Allah even though in detail the meaning is different. So in general, in their view, the Corona pandemic is seen as a warning as well as a punishment for humans depending on the context of its meaning.